2001
DOI: 10.1097/00003246-200104000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study of obstetric admissions to 14 intensive care units in southern England

Abstract: Existing databases can both identify critically ill obstetrical patients and provide important information about them. Obstetrical ICU admissions often require minimal intervention and are associated with low mortality rates. Many might be more appropriately managed in an HDU. The commonly used severity of illness scoring systems are good discriminators of outcome from intensive care admission in this group but may overestimate mortality rates. Severity of illness scoring systems may require modification in ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
97
4
27

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(146 citation statements)
references
References 36 publications
18
97
4
27
Order By: Relevance
“…The SOFA score offers several advantages [26][27][28][29][30]: it uses variables that can be easily measured without the need of very complex resources, proxy measures could be used in cases where complex or expensive variables cannot be measured, measurements can easily be standardized, and scores have high predictive and discriminatory ability in SMM. As in other studies [12][13][14][21][22][23][24]26], the maximum aggregated SOFA scores were prognostic, though in retrospect. In our study, the 95% confidence limits of the point estimates for the area under ROC curves of nearly all the systems showed that upper limits were >0.75 for all organs, indicates that severe obstetric morbidity is associated with multiple organ/system dysfunction.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The SOFA score offers several advantages [26][27][28][29][30]: it uses variables that can be easily measured without the need of very complex resources, proxy measures could be used in cases where complex or expensive variables cannot be measured, measurements can easily be standardized, and scores have high predictive and discriminatory ability in SMM. As in other studies [12][13][14][21][22][23][24]26], the maximum aggregated SOFA scores were prognostic, though in retrospect. In our study, the 95% confidence limits of the point estimates for the area under ROC curves of nearly all the systems showed that upper limits were >0.75 for all organs, indicates that severe obstetric morbidity is associated with multiple organ/system dysfunction.…”
Section: Discussionsupporting
confidence: 75%
“…Assessment of organ/system dysfunction is essential in the management of severe maternal morbidity (SMM) [6][7][8][21][22][23][24]. SMM refers to women with severe obstetric complications, some of whom die and others narrowly survive death (maternal near miss) [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported incidence of admission to the intensive therapy unit (ITU) varies between 0.17 and 2.6 per 1000 deliveries [1][2][3][4][5]. Notwithstanding the low incidence, the confidential enquiries into maternal and child health (CEMACH) from the United Kingdom highlight both delay and difficulty in recognising critical illness in mothers as a recurring theme prior to their referral for intensive care [6,7].…”
mentioning
confidence: 99%
“…Since 1991, large maternity units have been urged to provide centralised high dependency care with appropriately trained staff and the availability of invasive monitoring equipment ⁄ techniques [10]. More recently, the availability of high dependency unit (HDU) care for mothers in the delivery suite has shown a decrease in the number of ITU admissions, albeit not statistically significant [13], and that some ITU admissions might satisfactorily be cared for in an HDU setting [5]. Our objectives were to report our experience of HDU utilisation, including indications for admission, monitoring employed for mothers and whether babies accompanied their mothers as well as the need for ITU transfer.…”
mentioning
confidence: 99%